1984
DOI: 10.1037/0096-1523.10.6.778
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of the visual field.

Abstract: Three experiments investigated the identification or localization of a letter that was displaced from the fixation point by 1 degree-3 degrees. The subject's task was to identify a fixated letter and identify (Experiment 1) or localize (Experiments 2 and 3) the displaced letter. On uncued trials, the displaced letter could appear at any of eight locations on any of three rings surrounding the fixated letter; on cued trials, the ring containing the displaced letter was specified. The results indicated that cuin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
123
2
4

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(142 citation statements)
references
References 11 publications
13
123
2
4
Order By: Relevance
“…The primary dependent measures are accuracy and sensitivity (or discriminability). Perhaps because of technical problems similar to those discussed above, early studies using accuracy of form discrimination found relatively small effects, typically less than 5% (e.g., Egly & Homa, 1984;Grindley & Townsend, 1968;Van der Heijden, Schreuder, & Wolters, 1985). These were followed by numerous studies that indicated perceptual processing indeed may be better at cued locations than at uncued locations (e.g., Chastain, 1991;Downing, 1988;Muller, 1994;Muller & Findlay, 1987;Possamai & Bonnel, 1991;Shaw & Shaw, 1977).…”
Section: Spatially Cued Discrimination or Identificationmentioning
confidence: 99%
“…The primary dependent measures are accuracy and sensitivity (or discriminability). Perhaps because of technical problems similar to those discussed above, early studies using accuracy of form discrimination found relatively small effects, typically less than 5% (e.g., Egly & Homa, 1984;Grindley & Townsend, 1968;Van der Heijden, Schreuder, & Wolters, 1985). These were followed by numerous studies that indicated perceptual processing indeed may be better at cued locations than at uncued locations (e.g., Chastain, 1991;Downing, 1988;Muller, 1994;Muller & Findlay, 1987;Possamai & Bonnel, 1991;Shaw & Shaw, 1977).…”
Section: Spatially Cued Discrimination or Identificationmentioning
confidence: 99%
“…More recent studies have shown that localization variance increases when less attention is available (Adam, Huys, van Loon, Kingma, & Paas, 2000;Adam, Ketelaars, Kingma, & Hoek, 1993;Egly & Homa, 1984;Newby & Rock, 2001;Prinzmetal, Amiri, Allen, & Edwards, 1998;Tsal & Bareket, 1999). This has led theorists to propose that attention increases spatial resolution (He, Cavanagh, & Intriligator, 1997;Tsal, Meiran, & Lamy, 1995;Tsal & Shalev, 1996;Yeshurun & Carrasco, 1998).…”
Section: The Present Studymentioning
confidence: 99%
“…The sensitivity of perception is typically examined by utilizing signal detection theory. When a visual cue is presented beforehand to indicate the location of a target stimulus, the sensitivity for perception (either detection or discrimination) of the target becomes higher than otherwise equivalent stimulus which is not cued (Bashinski & Bacharach, 1980;Egly & Homa, 1984;Downing, 1988;Miiller & Rabbit, 1989). The changes in perceptual resolution can be measured as changes in positional accuracies, such as vernier acuity (Nakayama & Mackeben, 1989).…”
Section: Introductionmentioning
confidence: 99%